Гуманітарний чинник в роботі органів луцького міського управління в 1914-1918 рр. - Денисюк, Василь Іванович; Denysiuk, Vasyl I. (Інститут історії України НАН України, 2017)
Перед органами міського управління Луцька в роки Великої війни поставали проблеми забезпечення базових потреб лучан та гостей міста, що й становило гуманітарний фактор. У центрі дослідження перебувають питання гуманітарного характеру в місті Луцьк, а також діяльність органів міського управління в 1914 – 1918 рр. Виявлено, що проблеми гуманітарного характеру в цей час були зумовлені насамперед дефіцитом найнеобхідніших товарів, інфляцією, наявністю великої кількості біженців та переселенців, а також руйнацією в ході бойових дій, антисанітарією і труднощами фінансування. Головними проблемами гуманітарного характеру були поширення епідемій, продовольча криза та ін. Луцька міська управа намагалася нівелювати наслідки найбільш резонансних проблем, подекуди розв’язати власне проблеми. Складність подолання цих питань була пов’язана з об’єктивними чинниками війни, а також з браком коштів, низьким рівнем ініціативності керівників міста та відповідальності лучан.

Lutsk City administration in the war years faced the problem of satisfying basic needs of Lutsk citizens and the city guests, which made the humanitarian factor. The center of this research is humanitarian problems in Lutsk, as well as the city administration work in 1914-1918. The purpose of this article is to figure out the key humanitarian problems of the city in 1914-1918, as well as corresponding directions in the work of city council aimed to wipe off or level their influence. Due to the research held it was noticed that humanitarian problems in the city in 1914-1918 were caused, first of all, by the lack of some most necessary goods, exchange inflation, the presence of numerous refugees and immigrants, as well as by huge damage while military operations and lack of financing. The key humanitarian problems of the time were pandemic expansion, food crisis, etc. Lutsk city council was trying to level the consequences of the most resonant problems, sometimes even to solve the problems. The biggest difficulty was connected with the objective war factors, such as lack of finance, low initiative level from the city authorities and the inhabitants themselves. The research is built on the analysis of the original archive materials. An attempt has been made to separate and classify humanitarian problems, differentiate their reasons and results, as well as the specifics of the city authorities’ work in that direction. Except the research value in the area aspect, the example of this town is used to show the impact of damaging processes in economics and society on a person living at that time; the main difficulties have been shown in solving the key human needs while living in war conditions. Humanitarian problems in Lutsk in the war years can relatively divided into the following blocks of intertwined issues: 1) maintaining the key conditions for healthy existence; 2) social maintenance; 3) complex problems, connected with goods and their prices; 4) order processing in the town; life and property protection; 5) complex problem connected with the presence of refugees in the town; 6)improving the living conditions for the towns people by improving of public services and utilities. The town council prioritized maintaining the key conditions for healthy living of the townspeople as well as delivering most necessary goods (including food) and regulating their prices. However, a number of objective factors were in the way. For the further research development I think prospective comparison of data by Lutsk with the other towns of Volyn province in similar problems to determine the patterns and peculiarities.
Humanitarian factor in the work of lutsk town administration in 1914-1918
Keywords: Луцька міська управа; епідемія; біженець; проблеми управління; інфляція; дефіцит товарів; Lutsk city council; epidemic; refugee; management problems; inflation; shortage of goods